From Classification to Recreated 'Reality': William Bullock's Exhibitions of Human and Natural History. (20th November 2020) - Pearce, Susan
Abstract: In his London Museum (1809), William Bullock organised displays of his animal collections into family and contextual groups within re‐creations of their natural surroundings. Subsequently his displays of Saami material re‐created its social environment. Bullock's exhibitions signal a significant moment in the movement from the Linnaean‐style classification of natural material by appearance to explanation of it through contextual and inherent qualities. A new kind of meaning was generated, bringing together the natural and the antiquarian in showing that the same approach transformed understanding of both. It shifted emphasis from eighteenth‐century natural philosophy towards nineteenth‐century science, both natural and human.